Pengaruh Dakwah Ustaz Asyrofi terhadap Pemahaman Agama Islam Jamaah Masjid Al Ikhlas Dusun Koto Mandakek Desa Pauh Timur Pariaman - Saputra, Aidil; Setiawan, Daryanto; Gunawan, Candra (Asian Journal of Islamic Studies and Da'wah, 2025)
This study aims to analyze the effect of ustaz Asyrofi's preaching on the understanding of Islam among the congregation of the al ikhlas mosque in Koto Mandakek Hamlet, East Pauh Village, Pariaman. The population of this study amounted to 200 people with sampling done by simple random sampling technique or random sample with a total of 40 people. The research instrument used a questionnaire. The research data were processed and analyzed with the spearman rank correlation test using the help of SPSS 26 for windows. The results of the analysis showed that there was a significant influence between the variable of preaching ustaz Asyrofi on the understanding of Islam with a coefficient value of 0.429. These results indicate that preaching has a fairly strong influence on the understanding of Islam in Koto Mandakek Hamlet. For the significance test the results are significant or can be applied to the population because the significance value is 0.018 < than 0.05. then see the contribution of variable X to Y with the coefficient of determination formula, which is r2 x 100% = 0.1840 x 100% = 18.40%. While 81.60% is influenced by other variables that are not explained in this study.